Sorbate Density in 13x Zeolite - Al-Mousa, Alaa Marwan Subhi (2011)
A Master of Science Thesis in Chemical Engineering submitted by Alaa Marwan Subhi Al-Mousa entitled, "Sorbate Density in 13x Zeolite," submitted in June 2011. Available are both soft and hard copies of the thesis.